Stewardship Theory di antara hubungan corporate risk, kompensasi eksekutif, karakteristik eksekutif, dan kepemilikan saham pemerintah terhadap tax avoidance - Rahmad Efendi; Umi Muawanah; Kohar Adi Setia (Jurnal Ekonomi Modernisasi, 2022)
This research expected to understand the effect of corporate risk as measured by the standard deviation of EBITDA divided by total assets, executive compensation, executive characteristics as proxied by age and executive education and government share ownership on tax avoidance (ETR). The research sample of state-owned enterprises found on the official website bumn.go.id, was selected using the purposive sampling method, and 31 state-owned enterprises were obtained as observation data that met the sample criteria. The analysis to examine the effect of each independent variable on the dependent uses Multiple Regression. The results of the study state that corporate risk has a significant influence on tax avoidance, however, the results of this research are different when the researcher tries to exclude state-owned companies that are subject to final income tax from the research sample. From the results of this study, it was found that corporate risk has no effect on tax avoidance. executive compensation, executive characteristics of government share ownership have no effect on tax avoidance. Further research can use financial ratios, company age or other proxies that may affect tax avoidance. In addition, future researchers are expected to use private companies as a comparison of tax avoidance practices.